2017
DOI: 10.1039/c7sm01648d
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium mode-coupling theory for dense active systems of self-propelled particles

Abstract: The physics of active systems of self-propelled particles, in the regime of a dense liquid state, is an open puzzle of great current interest, both for statistical physics and because such systems appear in many biological contexts. We develop a nonequilibrium mode-coupling theory (MCT) for such systems, where activity is included as a colored noise with the particles having a self-propulsion foce f0 and persistence time τp. Using the extended MCT and a generalized fluctuation-dissipation theorem, we calculate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 62 publications
4
98
0
Order By: Relevance
“…Physically, this is because the dynamics is driven by pairwise interactions, controlled by the inter-particle distance as it can be read directly from the kernel expressions in Eq. (21).…”
Section: Effective Stochastic Process For the Inter-particle Distancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physically, this is because the dynamics is driven by pairwise interactions, controlled by the inter-particle distance as it can be read directly from the kernel expressions in Eq. (21).…”
Section: Effective Stochastic Process For the Inter-particle Distancesmentioning
confidence: 99%
“…The vector P (t) is only used to compute the response function, as in Eq. (21), and otherwise set to zero.…”
Section: Effective Stochastic Process For the Inter-particle Distancesmentioning
confidence: 99%
“…For sufficiently large persistence times, it was found that the fitted MCT glass transition temperature increases monotonically with increasing persistence time, suggesting that vitrification occurs more easily as the material becomes more active. An MCT-based scaling analysis for this type of active-matter system was later performed by Nandi and Gov [165]. Feng and Hou subsequently studied a thermal version of the active Ornstein-Uhlenbeck model that also includes thermal translational noise [109].…”
Section: B Mode-coupling Theoriesmentioning
confidence: 99%
“…Inspired by these active processes, a series of simulation studies have also been performed to build models for active polymers where monomers are treated as active Brownian particles (ABP) [8][9][10][11]. However, the dynamics of passive systems in active environment exhibit even more fascinating features [12][13][14]. A representative example of such system is an eukaryotic cell where proteins are constantly driven out of equilibrium by a range of active processes in addition to thermal fluctuations from surroundings [15,16].…”
mentioning
confidence: 99%